Preliminary development of a wearable device for dynamic pressure measurement in garments - McLaren, J.; Helmer, R. J. N.; Horne, S. L.; Blanchonette, I. (Procedia Engineering, 2010)
During activity, the body's limbs experience significant anthropometrical changes as muscles and tendons exert force for motion and stability. This dynamic motion is of interest to sports compression garment manufacturers who seek to enhance sports performance through gradient compression garment design. Existing devices for measuring garment pressure are generally not well suited to dynamic pressure measurement during sports activities due to limited portability, memory, communication and power capacity. A wearable wireless monitoring device was constructed, which included six 18mm diameter low profile pressure sensors that were placed on the body at various positions, e.g. on the calf, thigh, and buttocks regions, to sense garment pressure in the range of 5-50mmHg. The accuracy and precision of the wearable dynamic pressure monitoring device was explored using a series of step changes in pressure effected through the placement of a series of known masses. Similar tests were also conducted with the Kikuhime (TM) and PicoPress (TM) for comparison. Further tests to explore the performance of the wearable dynamic pressure monitoring device to monitor changes in pressure between a subject and garment during various activities were also performed. The performance of the wearable dynamic pressure monitoring device is discussed in terms of portability, dynamic response, accuracy, precision, resolution and general utility. It was generally found to be acceptable for further field studies. Wireless dynamic pressure monitoring devices represent a tool that could be utilised to help further understand and characterise dynamic compression in various sports activities. Such a device would enable functional testing and provide valuable information on dynamic compression values and the physiological efficacy of gradient compression garment design.